2004
DOI: 10.1074/jbc.m408398200
|View full text |Cite
|
Sign up to set email alerts
|

The Mutation F227I Increases the Coupling of Metal Ion Transport in DCT1

Abstract: Metal ion transport by DCT1, a member of the natural resistance-associated macrophage protein family, is driven by protons. The stoichiometry of the proton to metal ion is variable, and under optimal transport conditions, more than 10 protons are co-transported with a single metal ion. To understand this phenomenon better, we used site-directed mutagenesis of DCT1 and analyzed the mutants by complementation of yeast suppressor of mitochondria import function-null mutants and electrophysiology with Xenopus oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…S1, F-H). Overall, these trends are similar to the voltage dependence of mammalian Nramp2 Fe 2+ transport observed via electrophysiology (Gunshin et al, 1997;Chen et al, 1999;Nevo and Nelson, 2004;Xu et al, 2004;Mackenzie et al, 2006Mackenzie et al, , 2007Pujol-Giménez et al, 2017) and transport assays using radioactive Fe 2+ (Chen et al, 1999).…”
Section: Resultssupporting
confidence: 75%
“…S1, F-H). Overall, these trends are similar to the voltage dependence of mammalian Nramp2 Fe 2+ transport observed via electrophysiology (Gunshin et al, 1997;Chen et al, 1999;Nevo and Nelson, 2004;Xu et al, 2004;Mackenzie et al, 2006Mackenzie et al, , 2007Pujol-Giménez et al, 2017) and transport assays using radioactive Fe 2+ (Chen et al, 1999).…”
Section: Resultssupporting
confidence: 75%
“…We have recently reported that several members of a zinc trans-porter (ZNT) family are abundantly expressed in APP/ PS1 mouse brain (17). Together, with the present data, we provide the hypothesis that involvement of zinc in regulation of APP processing may be more related to the ZNT family rather than DMT1, although zinc transmembrane transportation is regulated by DMT1 (27). For ferric iron, it has been reported that DMT1 transports divalent (ferrous) iron, most likely produced by the reduction of ferric iron at the cell surface or within endosomal compartments (55), although there may be a separate pathway for ferric iron that does not rely on DMT1 (56).…”
Section: Dmt1 Regulates App Expression and Processingsupporting
confidence: 80%
“…Divalent metal transporter 1 (DMT1), also known as natural resistance-associated macrophage protein 2 (Nramp2) or divalent cation transporter 1 (DCT1), is a newly discovered proton-coupled metal-ion transport protein: the first mammalian transmembrane iron transporter (22). A widely expressed protein with 12 putative transmembrane-spanning domains, DMT1 is responsible for the uptake of a broad range of divalent metal ions, including Fe 2ϩ , Zn 2ϩ , Mn 2ϩ , Co 2ϩ , Cd 2ϩ , Cu 2ϩ , Ni 2ϩ , and Pb 2ϩ (22)(23)(24)(25)(26)(27). Four isoforms of DMT1 protein are distinguished through their variant mRNA transcripts that vary both at their 5Ј-UTR and 3Ј-UTR.…”
mentioning
confidence: 99%
“…Several studies have investigated the structure–function relationships in proteins of the NRAMP family (Lam‐Yuk‐Tseung et al ., ; Nevo and Nelson, , ; Courville et al ., ). Interestingly, analysis of the G185R mutation in the fourth transmembrane domain of NRAMP2/DCT1/DMT1, which leads to microcytic anemia in rat and mouse, demonstrated that this mutation not only impairs Fe transport but converts the transporter into a Ca‐permeable channel (Xu et al ., ).…”
Section: Introductionmentioning
confidence: 98%